Implementasi Kebijakan Digitalisasi Perpajakan Melalui Sistem Billing Coretax di Kabupaten Mamberamo Raya: Studi pada KPP Pratama Jayapura - Talemba, B. Aris; Marlissa, Elsyan Rienette; Muhdiarta, Untung (Jurnal Inovasi Global, 2026)
Digitization of tax administration through the Coretax platform is part of bureaucratic reform that aims to improve the efficiency of tax services. This study uses a qualitative descriptive approach with two main objectives, namely (1) analyzing the implementation of the tax digitization policy through the Coretax billing system in Mamberamo Raya Regency based on the George C. Edward III model which includes the dimensions of communication, resources, disposition, and bureaucratic structure, and (2) identifying factors that support and hinder its implementation. The results of the study show that the implementation of Coretax billing in general has run on the dimensions of communication, resources, disposition, and bureaucratic structure. Policy communication has been carried out through several channels, while the commitment of the implementer is an important element in maintaining the continuity of services. From the user side, this system provides benefits in the form of convenience, smooth service, and efficiency of tax administration. However, the implementation is not fully optimal because it is still influenced by the uneven understanding of taxpayers, low digital literacy, limited telecommunication infrastructure, electricity instability, and geographical conditions of the service area. Overall, the implementation of Coretax billing in Mamberamo Raya Regency shows an adaptive implementation pattern, where policy implementers play an important role in bridging the national digital system with local service conditions in the 3T area